Reform of Mathematics Education in Costa Rica: Evaluation of Progress in Implementation in Secondary Education: Reforma de la educación matemática en Costa Rica: evaluación de avance de la implementación en la educación secundaria - Meza Cascante, Gerardo (2019)
This article analyzes the level of consistency between the practice of the classroom and the approaches of the mathematics programs for secondary education approved by the Higher Council of Education in 2012, in relation to the resolution of problems as a main methodological strategy, active contextualization as a special pedagogical component and the intelligent and visionary use of digital technologies. This analysis was carried out through qualitative research in ten public schools with at least one from each province. As data collection techniques, non-participant observation, in-depth interview and focus groups were used.   The observation of lessons in the classroom made it possible to observe a lack of coherence between the dynamics developed and what the programs approved in 2012 propose. The teachers pose five elements that, in their opinion, make the successful implementation of the programs difficult: time available, the extension of the programs, the scarce access to technology, the need for training and the subject of evaluation. Additionally, they also pointed out other factors that hinder the application of programs such as large groups of students and some elements of the organizational culture, such as the guidelines or beliefs of the hierarchical superiors.   The results suggest that the implementation of the programs has been carried out without prior measures being taken, or at least in parallel, to address a series of factors that were identified as causes of the problem of mathematics education, and that precisely justified the change of programs, such as: aspects related to the working conditions of teachers, the institutional environment and the provision of teaching resources, appropriate for the new challenges, remain unanswered.  They also reveal the interest of teachers to reduce the amount of content of the programs, have fewer students in each group, improve access to technology as a teaching support, increase the number of weekly lessons and provide real joint planning time within the mathematics departments of each school. All of these are among the elements they consider relevant for a successful implementation of the programs. Teachers recognize the efforts made by the Ministry of Public Education to train them. However, there is a lack of conviction about the effectiveness of the training received, which means that teachers do not feel adequately trained to work with the programs.